A Study of Antenna System for High Order MIMO Device - Zhaoliang Chen; Wen Geyi; Ming Zhang; Jun Wang (International Journal of Antennas and Propagation)
Three types of compact MIMO (Multiple-Input Multiple-Output) antenna systems with four and six elements for mobile handsets are studied in this paper. The MIMO antenna system is built on a FR4 substrate of the dimensions 136 mm × 68.8 mm × 1 mm. The antenna element is a folded planar inverted-F antenna with added resonating branches wound on a small dielectric cube of the dimensions 10 mm × 10 mm × 5 mm, which is the smallest volume so far reported covering the frequency bands 1880 MHz–1920 MHz and 2300 MHz–2620 MHz for GSM1900, LTE2300, 2.4-GHz WLAN, and LTE2500. The effects of element numbers and configurations on the system performance are investigated. More than 10 dB isolations have been achieved by properly designing the antenna elements through the use of the pattern diversity without using decoupling circuits. The envelope correlation coefficients among the elements, the mean effective gains, the efficiencies, and the multiplexing efficiencies of the elements are also discussed.